Broadening the genotypic and phenotypic spectrum of MAF in three Chinese Han congenital cataracts families. Issue 10 (11th August 2022) - Wang, Qiwei; Qin, Tingfeng; Tan, Haowen; Ding, Xiaoyan; Lin, Xiaoshan; Li, Jing; Lin, Zhuolin; Sun, Limei; Lin, Haotian; Chen, Weirong
Abstract: Pathogenic variants in the v‐maf avian musculoaponeurotic fibrosarcoma oncogene homologue (MAF) encoding a transcription factor (from a unique subclass of basic leucine zipper transcription factors) are associated with isolated congenital cataracts (CCs) and Aymé–Gripp syndrome (AYGRPS). We collected detailed disease histories from, and performed comprehensive ophthalmic and systemic examinations in 269 patients with CCs; we then performed whole‐exome sequencing. Pathogenicity assessments were evaluated using multiple predictive tools. The clinical validities of the reported gene–disease relationships for MAF genes ( MAF ‐CCs and MAF ‐AYGRPS) were assessed using the ClinGen gene curation framework. We identified two novel (c.173C>A, p.Thr58Asn and c.947T>C, p. Leu316Pro) variants and one known (c.173C>T, p.Thr58Ile) MAF missense variant in three patients. We described novel phenotypes including cleft palate, macular hypoplasia, and retinal neovascularization in the peripheral avascular area and analyzed the genotype–phenotype correlations. We demonstrated associations of variants in the MAF C‐terminal DNA‐binding domain with CCs and associations of variants in the N‐terminal transactivation domain of MAF with AYGRPS. We thus expand the genotypic and phenotypic spectrum of the MAF gene. The ClinGen gene curation framework results suggested that variants in different domains of MAF are associated with different diseases.